Representation of Traditional Wisdom of Madurese Society in the Poetry Collection Rokat Perahu Mawar by Shohifur Ridho Ilahi: A Literary Anthropology Perspective - M. Helmi; Ahmad Yani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the representation of traditional wisdom embedded in the poetry collection Rokat Perahu Mawar by Shohifur Ridho Ilahi from the perspective of literary anthropology. Employing a qualitative descriptive method, this research examines words, lines, and stanzas that reflect the cultural values and traditional knowledge of the Madurese people. Data were collected through documentation techniques involving intensive reading, note-taking, and classification of textual data related to traditional wisdom. The analysis was conducted using content analysis and interpretative approaches grounded in literary anthropology, particularly focusing on the cultural roots and inherited traditions reflected in the poems. The findings reveal fifteen forms of traditional wisdom represented in eleven poems. These include kinship-based work ethics, the maritime tradition of amajâng (sailing), the sea as a source of life, grave pilgrimage traditions, respect for ancestors through bhuju’ (sacred tombs), the moral centrality of bhâbhu (mother), the symbolism of the celurit, salt production culture, rokat bhumè rituals, pèlèt betteng pregnancy ceremonies, coastal environmental preservation, beach-based social and cultural spaces, paparèghân traditional oral poetry, the symbolism of the perahu ba’, and the long-standing tradition of migration. These representations convey philosophical values concerning spirituality, social solidarity, environmental ethics, cultural identity, and the relationship between humans, nature, and the divine. This study concludes that Rokat Perahu Mawar functions not only as a literary work but also as a cultural archive that preserves and transmits Madurese traditional wisdom to contemporary society. Through poetic language, Shohifur Ridho Ilahi successfully transforms collective cultural memory into a literary medium that sustains local identity amid social and cultural change